What Drives the Voluntary Environmental Reporting (VER): An Examination of CDP India Firms - Kumar, Praveen; Firoz, Mohammad (Journal of Environmental Accounting and Management, 2026)
Environmental reporting is increasingly getting important in the value creation processes of the firms, but reporting standards are almost silent in this regard. Consequently, stakeholders need to rely on voluntary environmental reporting in order to better assess the environmental implications of the firms’ operations. We studied the determinants of voluntary environmental reporting (VER). Using a sample period from 2011 to 2015, we test whether and to what extent key firm and industry-specific variables such as size, the book to market value (BTMV), cross-border listing, ownership, industry, leverage, age, corporate governance and ROE can explain a firm’s probability of voluntary environmental reporting. The present study covered all 137 Carbon Disclosure Project (CDP) India firms, excluding banking and financial firms, amalgamated into nine different industry-sectors - Consumer Discretionary, Energy, Industrials, Information Technology,Materials, Telecommunication, Utilities, Consumer Staples and Health Care. By employing panel- data analysis this study revealed that Size, Cross Border Listing and age play a key role in explaining a firm’s voluntary environmental reporting policy across all industry sectors. Moreover, we also found a significant effect of the book to market value (BTMV), ownership, industry-sector, Leverage and Corporate governance on a firm’s voluntarily carbon disclosure. Further, the present study did not find any evidence to support that the sample firms’ profitability e.g. ROE affect the firms’ choice to voluntarily report their environmental activities. Moreover, voluntary environmental reporting by Indian firms is very low during sample period. The findings of this examination are crucial for managers, investors, regulators and standard-setters as they work toward developing standards for measuring, assuring, and reporting on a firm’s climate change actions.